2004
DOI: 10.1038/sj.cdd.4401359
|View full text |Cite
|
Sign up to set email alerts
|

Role of autophagy in temozolomide-induced cytotoxicity for malignant glioma cells

Abstract: Autophagy is originally named as a process of protein recycling. It begins with sequestering cytoplasmic organelles in a membrane vacuole called autophagosome. Autophagosomes then fuse with lysosomes, where the materials inside are degraded and recycled. To date, however, little is known about the role of autophagy in cancer therapy. In this study, we present that temozolomide (TMZ), a new alkylating agent, inhibited the viability of malignant glioma cells in a dose-dependent manner and induced G2/M arrest. At… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

47
815
5
10

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 912 publications
(877 citation statements)
references
References 35 publications
47
815
5
10
Order By: Relevance
“…To begin to examine the antitumor effect of TMZ on malignant glioma cell lines, unsychronized U251 GBM cells were first treated with TMZ (100 mM for 3 h) and further incubated for 3-14 days in the absence of TMZ, after which cells were analyzed by FACS for DNA content. Consistent with previous reports, [11][12][13] cells accumulated with 4N DNA content at the G2-M boundary, with ratio of 4N/2N DNA content peaking 3 days after TMZ treatment and decreasing gradually to base levels by 10 days post-TMZ exposure (Figures 1a and b).…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…To begin to examine the antitumor effect of TMZ on malignant glioma cell lines, unsychronized U251 GBM cells were first treated with TMZ (100 mM for 3 h) and further incubated for 3-14 days in the absence of TMZ, after which cells were analyzed by FACS for DNA content. Consistent with previous reports, [11][12][13] cells accumulated with 4N DNA content at the G2-M boundary, with ratio of 4N/2N DNA content peaking 3 days after TMZ treatment and decreasing gradually to base levels by 10 days post-TMZ exposure (Figures 1a and b).…”
Section: Resultssupporting
confidence: 92%
“…Consistent with previous reports, no apoptotic cells were detected microscopically or by cell cycle analysis (lack of cells with sub-G1 DNA content). [11][12][13] Finally, because recent investigations also demonstrated that radiation or chemotherapeutic agents including TMZ induce autophagy in malignant glioma cells, 13,14 we measured conversion of microtubule-associated protein 1 lightchain 3 (MAP1-LC3) (LC3-I, 18 kDa), to a lipidized form (LC3-II, 16 kDa) in TMZ-treated cells as a measure of autophagy. As shown in Figure 1d, TMZ induced an accumulation of the LC3-II form of MAP1-LC3 as early as 3 days after TMZ exposure, similar to what was noted following a 1-day exposure of the cells to the known inducer of autophagy, rapamycin.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, to block autophagy at early stages and prevent autophagosome formation, one could inhibit the Type III PI3 kinase complex with 3-methyl adenine or knockdown Beclin 1 or Atg5 with siRNAs, while to inhibit autophagy at later stages one could prevent fusion between the autophagosome and lysosome by knocking down or inhibiting Rab7 or use pharmacological agents such as the lysomotropic agent chloroquine or bafilomycin A1, an inhibitor of the vacuolar type H + ATPase. It may be important to discriminate between blocking autophagy at early or later steps because differences in outcome for the cell have been noted when this has been done (42). When the later stages of autophagy are blocked, the cell may accumulate large numbers of autophagosomes.…”
Section: Regulation Of Autophagymentioning
confidence: 99%
“…The cytotoxic effect of TMZ can be affected by complex molecular pathways 20. Herein, we observed that the expression of FBW7 was markedly inhibited at both protein and mRNA levels in U251/TMZ, a cell line which was isolated in our previous experiment with 4‐fold 50% inhibition rate (IC50; data not shown), compared to the parental U251 cell line ( P ‐value <.01 for quantitative RT‐PCR, Figure 3A,B), suggesting the potential role of FBW7 in mediating TMZ response.…”
Section: Resultsmentioning
confidence: 99%